2005
DOI: 10.1523/jneurosci.3912-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Regulatory Element Antagonist Modulator Regulates Ca2+Homeostasis and Viability in Cerebellar Neurons

Abstract: The Na+/Ca2+ exchangers NCX1, NCX2, and NCX3 are vital for the control of cellular Ca2+ homeostasis. Here, we show that a doublet of downstream regulatory element sites in the promoter of the NCX3 gene mediates transcriptional repression of NCX3 by the Ca2+-modulated transcriptional repressor downstream regulatory element antagonist modulator (DREAM). Overexpression of a DREAM EF-hand mutant insensitive to Ca2+ (EFmDREAM) in hippocampus and cerebellum of transgenic mice significantly reduced NCX3 mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 32 publications
3
105
1
Order By: Relevance
“…Especially KChIP3, but also KChIP1, KChIP2 and KChIP4, may fulfill the function of a transcriptional repressor, either directly, by binding to downstream regulatory element (DRE) sites of genes [19,5561], or indirectly, by binding to other transcription factors [6264]. Here the focus is put on direct KChIP-mediated control of gene transcription (Figure 1C), which appears to be commonly linked to excitability.…”
Section: Kchips Control Gene Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially KChIP3, but also KChIP1, KChIP2 and KChIP4, may fulfill the function of a transcriptional repressor, either directly, by binding to downstream regulatory element (DRE) sites of genes [19,5561], or indirectly, by binding to other transcription factors [6264]. Here the focus is put on direct KChIP-mediated control of gene transcription (Figure 1C), which appears to be commonly linked to excitability.…”
Section: Kchips Control Gene Transcriptionmentioning
confidence: 99%
“…Thus, in nociceptive spinal cord neurons the prodynorphin gene is switched on during massive action potential firing with elevated cytoplasmic Ca 2+ levels, to modulate pain perception via κ-opioid receptors [19,41,65]. In an analogous manner the Na + /Ca 2+ exchanger (NCX) 3 expression in cerebellar neurons is under the control of the transcriptional repressor KChIP3 (DREAM), which may occupy a doublet of DRE sites in the NCX3 gene when Ca 2+ is low [55]. Dissociation of KChIP3 (DREAM) from these DRE sites in an EF-hand-dependent manner and activation of the NCX3 gene occurs if cytoplasmic Ca 2+ is elevated, which has been interpreted as a negative feed-back control loop of Ca 2+ homeostasis [55].…”
Section: Kchips Control Gene Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NCX3 was shown to be more relevant for cell survival than NCX1 or NCX2, namely in cultured cerebellar granule neurons. 14, 15 We recently reported that neurotoxicity induced by activation of AMPA receptors is characterized by calpain activation, lack of caspase activation, nuclear condensation/fragmentation, release of cytochrome c from mitochondria, decreased intracellular ATP levels, production of nitric oxide, moderate superoxide production and increased levels of peroxynitrite. [16][17][18] In this in vitro model of excitotoxicity, the cell death mechanisms are mostly dependent on calpains, 11 providing a good model for studying calpain-dependent phenomena.…”
mentioning
confidence: 99%
“…Downstream regulatory element antagonist modulator (DREAM), which was first identified as a Ca 2ϩ -regulated transcriptional repressor, contains four Ca 2ϩ -binding EF hand domains and belongs to the neuronal calcium sensor (NCS) family (Carrió n et al, 1999;Burgoyne, 2007). DREAM was named for its ability to block gene expression in its Ca 2ϩ -free form via direct binding with the downstream regulatory element sequence in target genes such as preprodynorphin, c-fos, Hrk, and Na ϩ and Ca 2ϩ exchanger NCX3 (Carrió n et al, 1999;Sanz et al, 2001;Gomez-Villafuertes et al, 2005). DREAM was also named calsenilin or potassium channel-interacting protein 3 (KChIP3) (Buxbaum et al, 1998;An et al, 2000), suggesting that it has multifunctional properties.…”
Section: Introductionmentioning
confidence: 99%